FRI0013 Open-label evaluation of the efficacy and safety of etanercept in common rheumatology usage (ecru). (1st June 2001) - Herold, M; Aytekin, A; Klein, G; Nowak, J; Siegmeth, W; Stuby, U
Abstract : Background: Tumour Necrosis Factor-alpha (TNFα) plays an important role in the inflammatory processes of RA and the resulting joint pathology. Etanercept is a dimeric fusion protein consisting of two p75 TNFα receptors linked to the Fc portion of the human IgG1. This protein can bind and inactivate up to two free molecules of TNFα. The safety and efficacy of etanercept has been demonstrated in human clinical trials of early RA and active RA. Objectives: The Primary efficacy variable was the proportion of patients achieving 20% improvement in symptoms according to American College of Rheumatology (ACR) response criteria at Week 16. Patients were evaluated clinically for adverse events at each visit. Methods: This study was conducted in 55 Austrian outpatients with active RA who have failed at least one disease-modifying anti-rheumatic drug (DMARD). Each patient received twice-weekly subcutaneous injections of etanercept 25 mg administered over a treatment period of 16 weeks. Stable doses of methotrexate (MTX) and steroids were permitted. A clinical assessment of the patient's response to therapy and safety assessments were performed at each regular visit. Results: Efficacy: At week 16, 80% of the patients achieved an ACR 20 response (primary outcome measure). Moreover, 45, 5% of patients achieved an ACR 50 response and 10, 9% patients achieved an ACR 70 response at week 16. The mean number of swollen joints fell from 17 at baseline to 6, 7 at week 16. The mean number of tender joints fell from 18, 9 at baseline to 7, 1 at week 16. The mean score of Patient's Global assessment fell from 6, 6 at baseline to 2, 9 at week 16. The mean score of Physician's Global Assessment score fell from 6, 5 at baseline to 2, 7 at week 16. Safety: Etanercept 25 mg twice weekly was well tolerated. Adverse Events were primarily mild injection site reactions. Conclusion: This was an open-label, uncontrolled, 16 week study conducted in 55 Austrian RA patients for whom DMARD therapy was inappropriate or ineffective. Stable doses of MTX and steroids were allowed. The percentage of patients with an ACR 20 response in the present study (80%) is slightly greater than that reported in prior large multicentre studies (range 70‑75%). No unusual patterns of AEs were identified. The safety and efficacy of etanercept 25 mg s.c. twice weekly in a single European country in a naturalistic, "common usage" setting were similar to that observed in controlled clinical trials in the US and EU.